2022
DOI: 10.24034/jiaku.v1i1.4949
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Profitabilitas, Leverage, Dan Kepemilikan Institusional Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening

Abstract: The existence of competition requires companies to make various efforts to maintain the existence of the company and increase company value. The company value is indicated by the company's stock price. The purpose of this research is to prove empirically the effect of profitability, leverage and institutional ownership on firm value with dividend policy as an intervening variable. The research data is secondary data in the form of financial statement data and annual reports of companies belonging to the manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Dang et al [23] revealed that dividend policies has a positive and influential impact on company value. In addition, empirical studies by Astuti and Yadnya [15], Setyabudi [19], Sari et al [18], and Santosa et al [26] demonstrates that dividend policies has been shown to have a positive and influential impact on company value.…”
Section: Dividend Policy and Firm Valuementioning
confidence: 99%
See 3 more Smart Citations
“…Dang et al [23] revealed that dividend policies has a positive and influential impact on company value. In addition, empirical studies by Astuti and Yadnya [15], Setyabudi [19], Sari et al [18], and Santosa et al [26] demonstrates that dividend policies has been shown to have a positive and influential impact on company value.…”
Section: Dividend Policy and Firm Valuementioning
confidence: 99%
“…[18], and Setyabudi [19] demonstrates that profitability and leverage were found to have a favorable and substantial effect on dividend policies. Then, empirical studies by Rahmasari et al [20] found that liquidity has a strong and beneficial impact on dividend policies.…”
Section: Financial Performance and Dividend Policymentioning
confidence: 99%
See 2 more Smart Citations
“…According to (Setyabudi, 2022) the definition of profitability ratio is a ratio to assess the company's ability to seek profit. This ratio also provides a measure of the level of management effectiveness of an enterprise.…”
Section: Profitability Ratiomentioning
confidence: 99%